CULTURAL COMMODIFICATION: REPRESENTATION OF PESAREAN1 OF MOUNT KAWI AS CULTURAL TOURISM IN INDONESIAN MASS MEDIA - Dwi Sulistyorini; Bani Sudardi; Warto Warto; Mahendra Wijaya (Jurusan Sastra Indonesia, 2017)
Media is a tool to construct meaning to its readers. News that is released to the public is always related to the ideology and interests of the media in responding a problem. This research intends to see a representation of Pesarean of Mount Kawi which is conducted by local, regional, and national mass media in Indonesia. This research is a qualitative research with content analysis method. This study is going to be focused on the value embedded in texts which contain news about pesarean of Mount Kawi. This approach is very useful to figure out meaning that lies behind the news texts of pesarean of Mount Kawi. The result of the research shows that mass media supports the commodification process of pesarean of Mount Kawi. Through the narration of origin, genealogy, and heroism which are based on Indonesia's national historical event became one of the strategies that are used to demolish the representation of Mount Kawi as a haunted and taboo place to be visited by society. There is a similarity of vision in changing the representation of pesarean of Mount Kawi. Modernity and advancement of reasons have been the reasons for discarding cultural values and traditions that have developed within the culture of Javanese society for centuries by adapting them to the contexts of modern human life today.